The effect of stress towards job performance in public organizations / Rosemawati Asri - Asri, Rosemawati (2004)
The purpose of this study is to study on the level of stress towards job performance face by the government servant in Jabatan Kastam Diraja located in Ayer Keroh, Melaka.